Pengaruh Good Corporate Governance Terhadap Kualitas Laporan Keuangan Pada PT. Mandiri Indonesia Agam Kota Palembang - Nandita; Citra Indah Merina (Masyarakat Ekonomi Syariah Bogor, 2025)
The purpose of this research is to test and analyze the Influence of Corporate Governance on the Quality of Financial Statements at PT. Mandiri Indonesia Agam Palembang City. This type of research is a quantitative approach with the type of research used in primary data. The data obtained uses primary data. Data was obtained through filling out questionnaires. The research sample consisted of 111 respondents who were selected using total sampling. The results show that there is a significant influence on the quality of financial statements at PT. Mandiri Indonesia Agam Palembang City. Data analysis was carried out using SEM PLS version 4.0 and analyzed with the help of Smart PLS, involving the Measurement Model Analysis Test (outer model) and the Structural Model Analysis Test (Inner Model). The results of the study show that Corporate Governance has a significant influence on the quality of financial reports with a loading factor of > 0.7 which means Valid.